KONSTRUKSI HUKUM PEMBERIAN HAK GUNA BANGUNAN DAN HAK PAKAI DI ATAS TANAH KRATON DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - , Athanasia Dian Santi, S.H; , Prof. Dr. Maria SW Sumardjono, S.H., MCL., MPA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This thesis deals with the legal concept of the granting of land right of Sultan Grond to the third party according to Basic Agrarian Law focuses on the background of the issuance of the Letter of Head of National Land Agency No. 570.342493 of October 21st, 2003, the practice of the granting of the right of building and the right of use based on the Letter of Head of National Land Agency, obstacles and problems faced. Secondary data in the form of document and the results of field research are analyzed using descriptive-qualitative method in order to answer the research problems. The results of the study show that: 1. the background of the issuance of the Letter of Head of National Land Agency No. 570.342493 is to provide a legal basis for the people who will utilize Sultan Grond. 2. the practice of granting land to third parties by utilizing Magersari right and Pinjam Pakai right has taken place for a long time. Those two rights are different: Magersari right is granted to Abdi Dalem, while Pinjam Pakai right is granted to people other than Abdi Dalem. Duration of both rights are 10 years and can be extended. Especially for Regional Government, the duration is 15 years. 3. the mechanism of the granting of the right of building/ the right of use based on the Letter of Head of National Land Agency No. 570.342493 of October 21st, 2003 contains asumtion of Kraton as the holder of the right of ownership and the right of anagement since the Letter of National Land Agency does not clearly state the legal position of Kraton Yogyakartaâwhether as holder of the right of ownership or holder of the right of management, or holder of Ulayat Land. This obscurity can be seen from the process of the registration of the right of building/ the right of use in which one needs two basic letters, namely Surat Kekancingan- between Kraton and third parties- and the Decision of Granting of Right by Officials of the Land Agency. 4. The obstacles in the granting of land right to third parties are: first, the administrative completeness and legal event of the applicant